The role of hydrogen bonds on the mechanical properties of cement-based mortars applied to concrete surfaces. (January 2021) - Berenguer, R.A.; Lima, N.B.; Lima, V.M.E.; Estolano, A.M.L.; Póvoas, Y.V.; Lima, N.B.D.
Abstract: Hydrogen bonds are important chemical interactions that influence several properties, such as the adhesion ability of cement-based mortars applied to concrete substrates. In this sense, in the present article, the role of the presence of hydrogen bonds on the mechanical properties of a set of mortars (weak, intermediate, and strong) is advanced. The mechanical performances were the compressive, flexural, and adhesion strengths. The results revealed linear correlations (R 2 > 0.97) between these mechanical properties and the energetic nature of the hydrogen bonds present in the mortar pastes. Besides, the energetic strength of the hydrogen bonds also affects the adhesion mechanism of the cement-based mortars applied to both concrete and roughcast/concrete substrates. Further, SEM/EDS analyses revealed chemical aspects of the surfaces of the mortars, and the quantities of Ca, O, and Si, which can affect the ability of adhesion between the mortar coating and a solid substrate. In conclusion, the role of hydrogen bonds on the set of investigated mechanical properties of the cement-based mortars can be rationalized as follows: (i) weak hydrogen bonds present in the mortar pastes are associated with large mechanical performances, and (ii) strong hydrogen bonds are associated with poor mechanical performances of these materials. Highlights: The role of hydrogen bonds in the mechanical properties of mortars is advanced. R 2 > 0.97 values were verified for the mechanical and hydrogen bond properties. The hydrogen bond strength affects the adhesion of the mortars applied to concrete. The Ca, O, and Si quantities in the mortar surfaces affect their adhesion ability. Weak hydrogen bonds are associated with large mechanical performances.